Caring for newborns in a NICU: dealing with the fragility of living/surviving in the light of complexity - Klock, Patrícia; Erdmann, Alacoque Lorenzini (Revista da Escola de Enfermagem da USP, 2012)
The objective of this study was to understand the meaning of being a nurse and providing care in the Neonatal Intensive Care Unit (NICU) of a general hospital in Southern Brazil, developing an explanatory theoretical model. The Grounded Theory and the Complexity Paradigm were used to develop the Theoretical Model: Caring for newborns in the NICU: Dealing with the fragility of living/surviving in the light of complexity. Data was collected from 11 subjects through an open interview, and organized using NVIVO software. A central category was identified: Dealing with the fragility of living/surviving: a care that is highly complex, sensitive, unique and shared. Care in the NICU, valuing the everyday interrelationships, aims to address all domains of complex health care, integrating and applying scientific knowledge. It is necessary to practice the strengths already inherent to nursing professionals, in addition to pursuing new strengths, an invitation to new models of care for newborns, their family, and the members of this complex system.